Parameter optimization of crude palm oil transesterification using response surface methodology - Noraini, Mat Hussin; Maniam, Gaanty Pragas; Mohd Hasbi, Ab Rahim (AIP Publishing, 2024)
As a promising and cost-effective alternative to diesel fuel, biodiesel holds the potential to reduce global reliance on petroleum fuel imports. As one of the potential feedstocks to produce biodiesel, crude palm oil with a low acid value was subjected to transesterification with methanol and an alkaline catalyst. The catalyst, potassium hydroxide (KOH), was standardized to determine the accurate molarity prior to the reaction. The parameters for transesterification process including methanol to oil ratio (9-15), catalyst loading (1.5-2.5 wt.%), and reaction time (60-90 min) were optimized using Central Composite Design employing Response Surface Methodology. The transesterification reactions were performed at the refluxing temperature of methanol. For identification, gas chromatography with mass spectrometry was employed, while gas chromatography with a flame ionization detector was utilized for quantification of the methyl ester. The design revealed that the optimal methanol to oil ratio was 10.9:1, catalyst loading of 2.26 wt.%, and the reaction time was 90 min. The conversion of crude palm oil to methyl ester efficiently achieved a maximum of 97.58% under the ideal conditions. Furthermore, the biodiesel was characterized and found to meet the specific standard for biodiesel as specified in the ASTM D6751 and EN 14214. Through this study, an optimum condition for producing biodiesel from crude palm oil was successfully developed.